Environmental management system in Ventanilla District - Alvarado Moreno, José Luis (2019)
The town Mi Peru currently has a population of 43,000 inhabitants and a total area of 1,89 km2. An alternative for a Municipal Environmental Management focus on the and with a clear focused of the community is presented. Municipal Environmental Management should be deemed as an important tool for the overall management of the municipality and to get we must internalize the concept and accept the inclusion of variables and environmental factors. In this research three aspects were prioritized: 1) the Environmental Diagnosis to define the environmental quality index in the town Mi Peru; 2) the conceptual and theoretical framework of the Municipal Environmental Management, the different instruments, the implementation of the study area; 3) The proposed Environmental Management System, which is defined as integrating its structure and operation. Finally, findings, conclusions and recommendations are described.